Yoruba ontology: perception of the physical body of the dead and its implications for cadaveric organ transplantation in south-west Nigeria - Awobusuyi, Jacob O (African Journal of Nephrology, 2022)
Introduction: The perception of death differs by region, culture, religion, and ethnic group in Nigeria. These differences can affect the consent rate for cadaveric transplantation. Understanding the Yoruba concept of death and approaching families for consent in a culturally sensitive manner may increase family consent to deceased donor organ harvesting. This literature review explores the Yoruba concept of death and organ transplantation. Methods: Three research questions were formulated and a search strategy was drafted by creating a SPIDER (Sample, Phenomenon of Interest, Design, Evaluation, and Research type) logic search grid. Relevant databases were then examined using the search terms, concepts and keywords so generated. The findings of publications retrieved on Yoruba beliefs regarding death were entered into a summary table based on the themes identified in them. These themes served as the basis for the interpretation synthesis. Results: Fifteen of the eighty-five studies identified initially were deemed contextually relevant to the researchquestions and used in the analysis. These sources revealed that death in the Yoruba belief system signifies the dematerialization of the soul and its transformation from earthly existence into a spiritual one. Consequently, the physical body of the deceased is perceived as becoming dust and of little relevance to the afterlife. Conclusion: In the Yoruba worldview, the state of the physical body after death has no relevance to afterlife and reincarnation. However, transplant teams must consider the circumstances of death when asking for consent. When death is viewed positively, success is more likely.